2014
DOI: 10.1007/s00127-014-0843-y
|View full text |Cite
|
Sign up to set email alerts
|

Service use in adolescents at risk of depression and self-harm: prospective longitudinal study

Abstract: Most adolescents at high risk of depression or self-harm see their GP over a 6-month period although only a minority of them access specialist mental health services. Their consultations within primary care settings provide a potential opportunity for their identification and for signposting to appropriate specialist services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Older adolescents are more likely to initiate help-seeking in their own right. The higher rate of primary care contact for SH in older adolescents may be partially attributable to an increase in help-seeking with age 33…”
Section: Discussionmentioning
confidence: 99%
“…Older adolescents are more likely to initiate help-seeking in their own right. The higher rate of primary care contact for SH in older adolescents may be partially attributable to an increase in help-seeking with age 33…”
Section: Discussionmentioning
confidence: 99%
“…It is important therefore that the issues relating to service access and use are considered in future research. A survey of UK adolescents at high risk of self‐harm found that few had accessed specialist mental health services but that the majority had seen their general practitioner during the preceding six months (Sayal, Yates, Spears & Sallard, ). Furthermore, research indicates that alexithymia is significantly associated with high use of health care services and frequent reporting of symptoms (Lumley, ).…”
Section: Discussionmentioning
confidence: 99%
“…18 Additionally, 58% of young people who engage in self-harm had seen their GP in the previous 6 months. 20 As such, primary care presents a valuable opportunity for the identification, response to, and management of signs of suicidal behaviour and self-harm in young people. 21 Training standards for general practice recommend that GPs are able to identify warning signs and risk factors for suicide and respond appropriately.…”
Section: Open Accessmentioning
confidence: 99%